2017
DOI: 10.1186/s13054-017-1860-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sex and age on neurological outcomes in out-of-hospital cardiac arrest patients with targeted temperature management

Abstract: BackgroundThere are conflicting data regarding sex-based differences in the outcomes of out-of-hospital cardiac arrest (OHCA) patients, and whether the specific sex advantage is age-specific remains unclear. We assessed the impact of the interactions between sex and age on the neurological outcomes of OHCA patients receiving targeted temperature management (TTM).MethodsData collected from 2007 to 2012 for a multicenter, registry-based study of the Korean Hypothermia Network were analyzed. We used a multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
1
23
1
Order By: Relevance
“…Patient level characteristics, such as age, sex, and underling diseases are also prognostic factors of OHCA [6][7][8][9][10]. However, the in uence of comorbidities on cardiac arrest outcomes is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Patient level characteristics, such as age, sex, and underling diseases are also prognostic factors of OHCA [6][7][8][9][10]. However, the in uence of comorbidities on cardiac arrest outcomes is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Men are disproportionately affected by OHCA, with a greater representation in OHCA studies. 1,[4][5][6][7][8][9][10] Men have a higher prevalence of coronary artery disease and cardiomyopathy, which are the primary causes of OHCA in adults. 1 Baseline characteristics of male and female OHCA victims differ, with women typically being older and displaying a lower prevalence of favorable arrest circumstances such as witnessed arrest, shockable arrest rhythm, and cardiac etiology.…”
mentioning
confidence: 99%
“…1 Baseline characteristics of male and female OHCA victims differ, with women typically being older and displaying a lower prevalence of favorable arrest circumstances such as witnessed arrest, shockable arrest rhythm, and cardiac etiology. [4][5][6][7][8][9][10] The results of recent studies conflict regarding the association between the sex of OHCA victims and OHCA outcomes, particularly after adjustment for baseline differences. [4][5][6][7][8][9][10] A 2015 metaanalysis of older studies demonstrated higher survival among female OHCA victims (adjusted odds ratio [OR]¼1.1) after adjusting for their higher age and lower rates of shockable rhythms and witnessed arrest.…”
mentioning
confidence: 99%
See 2 more Smart Citations